Developing Learning Model â€œProject-Based Learning in Improving the Handycrafting Subject for Junior Hgh Schoolâ€ (Journal of Vocational and Career Education, 2019)
The objective of the study was to analyse the validity of the project-based learning model in the handycrafting subject learning in Junior High School and analyze the effectiveness of the project-based learning model in improving the creativity of students. The method used in this study was research and development (RD), using ADDIE with product developed is handycrafting project-based learning. This research produces an assessment instrument in the form of a test used for measuring cognitive domains, while non-performance tests (performance tests) are used to measure the affective domains (cre ativity) and psychomotor (skills). Product validity is done by using the CVR validity test with the results of 0.736 kappa reliability results with 2 expert tests 0.7 with Kappa reliability test and the effectiveness of the competency test model using T Test analysis. The results of the Project Based Learning development model for handycrafting subject addressed for VII grader students of Junior High School showed three assessments involving cognitive, affective and psychomotor assessments . The effectiveness of the competency test model showed that knowledge 20%, attitude 35%, and skills 85% which resulted that this development model is able to assess students effectively and objectively. The benefits of this research can be a motivation for students in learning and can be made a guideline for educators in assessing students.